A stretchable and human-compatible triboelectric nanogenerator integrated with LiCl liquid electrode for volleyball monitoring - Li, H. (Journal of Electronic Materials, 2022)
The growth of wearable electronic devices, such as electronic skin, human health monitors, and intelligent sports sensors, has resulted in a significant increase in the demand for sustainable power sources. In addition, traditional motion sensors rely on power supply to work normally, which limits their use scenarios. In this work, we propose a novel flexible triboelectric nanogenerator with shape adaptation and extensibility (SE-TENG) that utilises LiCl solution for its biocompatibility, conductivity, and long-term stability as the working electrode for mechanical energy harvesting and volleyball sports monitoring. From the results, the open-circuit voltage (Voc) of SE-TENG can arrive at 360 V, and the short-circuit current (Isc) of SE-TENG can arrive at 21 mA m-2. In addition, the maximum output power of SE-TENG can reach 2.4 W m-2. As a motion sensor, the SE-TENG can obtain movement information of various parts of the human body in volleyball motion, such as elbow, knee, and wrist. It is also possible that SE-TENG gathers biomechanical power from arm tremors, human movement, fist-clenching, and other sources in order to run industrial electronic gadgets without any need for external power sources. As a result, the flexible SE-TENG with LiCl liquid electrode is a fascinating base for biomechanical power generation and a wearable sports sensor.